CULTPOP: strategies and experiences for science and pop culture popularization - Amaral, Adriana; Blanco, Beatriz; Govari, Caroline; Cordova, Jonara; Tabasnik, Rafaela; Caetano, Stella; Larrubia, Tatyane; Becko, Larissa Tamborindeguy (Comunicação & Educação, 2023)
This experience report addresses the scientific popularization strategies employed in activities developed by the CULTPOP – Research Laboratory in Pop Culture, Communication and Technologies, linked to CNPq and currently based in the Graduate Program of Universidade Paulista (UNIP). It presents an overview of science popularization strategies organized based on the specific dynamics of the group’s research, as well as the use of pop culture’s own languages as part of its methodological process. The exploratory and descriptive case study indicates that having a laboratory community of academic-fans of pop culture facilitates and expands the development of science popularization strategies.